PROGETTO MIAPI MONITORAGGIO E INDIVIDUAZIONE DELLE AREE POTENZIALMENTE INQUINATE - Petriglia, Laura; Peloso, Christian; Costabile, Salvatore (GEOmedia, 2015)
The MIAPI Project (Detection And Monitoring Of Potentially Polluted Areas) is a cooperation between the Carabinieri Force and the Ministry of the Environment. The project, focused on the Italian Regions Campania, Calabria, Apulia and Sicily, aims to provide information for fighting environmental crimes. The project has been organized in three stages. The first one is a multiple-criteria analysis for the identification of areas potentially involved in environmental crimes. Airborne operations are part of the second stage, which includes multi-sensor surveys (gamma spectrometer, magnetometer, thermal and photogrammetry) on an area of 12000 km2. All acquired data are then analysed for the detection of possible anomalies in physical and geophysical parameters in order to plan ground surveys on specific target. If ground surveys are positive, the area is exactly delimited and classified. The third and last stage is the creation of an information system called SIAPI. SIAPI, implemented by the Ministry of the Environment, is updated and feed by the Regional Environmental Protection Agencies and the Carabinieri Force. Since a huge interest grew in the Project MIAPI, in October 2014 a contract was signed for providing additional 8,000 km2 of aerial.